Improved far-field blast predictions from fast deflagrations, DDTs and detonations of vapour clouds using FLACS CFD. (May 2015) - Hansen, Olav R.; Johnson, D. Michael
Abstract: The CFD tool FLACS was developed from 1982 with a primary goal to predict gas explosion loads inside oil platform modules. The prediction of far-field blast loads was of secondary importance as any scenario creating a substantial far-field blast would already have collapsed the module where it originated. For the same reason the potential for a deflagration-to-detonation-transition (DDT) was not initially of interest. Over the past decade use of FLACS has been more widespread, and the tool is now frequently used to predict explosions on onshore facilities and FPSOs/FLNGs, where far-field blast loads and evaluation of DDT potential may be of significant interest. Previous work by Hansen et al. (2010) has highlighted a weakness in FLACS when predicting the far-field blast from strong gas explosions and, when using FLACS according to guidelines, far-field blast pressures will often be significantly underpredicted. For scenarios involving DDT this effect will be particularly strong. The current study will present a way to obtain more accurate far-field blast predictions by modified parameter settings in FLACS for strong deflagrations. Using modified settings, it is also possible, with good precision, to predict flame speeds, pressures and far-field blast from DDT-scenarios and directly initiated gas detonations, physics which are beyond the accepted capabilities of FLACS. Selected full-scale experiments from the DNV GL test site at Spadeadam will be used to compare with the simulations. Convincing evidence for DDT in large scale natural gas experiments (91% methane) was found in simulations of one of these tests.